The Scope of an Employee’s Informational Autonomy Regarding Data Concerning Religion - Kuba, Magdalena (Acta Universitatis Lodziensis. Folia Iuridica, 2025)
The aim of the article is to attempt to assess the scope of an employee’s informational autonomy regarding data concerning religion, taking into account the legal conditions resulting from both European law and national regulations. The author analyses the admissibility of the employer processing information on the employee’s religion as a circumstance determining the scope of the employee’s freedom to disclose the above data. He considers this issue in particular in the context of granting employees a day off to celebrate religious holidays, noting that the regulations concerning this issue do not provide the authorisation for the employer to process data on religion, and therefore do not meet the requirements specified in art. 9 par. 2 let. b of GDPR.